Political advertising in the 2014 European Parliament elections - Holtz-Bacha, Christina ; Novelli, Edoardo ; Rafter, Kevin (Palgrave Macmillan, 2020)
Machine generated contents note: |g1.|tIntroduction /|rKevin Rafter -- |g2.|tBackground to the 2014 Elections /|rKevin Rafter -- |g3.|tRegulation of Electoral Advertising in Europe /|rChristina Holtz-Bacha -- |g4.|tRepresentations of the European Project /|rFrancisco Seoane Perez -- |g5.|tRepresentations of the Economic Crisis and Austerity Politics /|rCarmen Sammut